Abnormal uterine bleeding and severe anemia cause the life-threatening condition - D, Bursać; Diana, Culej; G, Planinić Radoš; J, Župan; P, Perković; Ž, Duić; S, Gašparov (Clinical Journal of Obstetrics and Gynecology, 2022)
The World Health Organisation (WHO) defines anemia as a global public health problem. It is a medical condition in which the number of red blood cells or the hemoglobin concentration within them is below the physiological range. We present a case of a 40-year-old woman with Abnormal Uterine Bleeding (AUB) accompanied by malaise, weakness, and tachycardia. The patient reported heavy menstrual bleeding for the past 14 days. Speculum examination revealed that the bleeding was from the uterus. There were no pathological findings during a gynecological and transvaginal ultrasound examination. A complete blood count performed at the time of her arrival showed a low hemoglobin level of 24 g/L, a low hematocrit level of 7,4%, a mean corpuscular volume of 98,7 fL and a number of red blood cells 0,75 x 1012/L. Due to the severity of the anemia, she was given 6 units of red blood cell transfusion, 2 fresh frozen plasmas and tranexamic acid accompanied with calcium carbonate. The curettage was performed. The pathohistological finding was endometrium in proliferation. Afterward, the hemoglobin level increased to 90 g/L. Their past medical history revealed that she abused alcohol. On an abdominal CT scan, Alcohol-Related Liver Disease (ARLD) was confirmed. We should keep in mind that coagulopathy could be the underlying cause of abnormal uterine bleeding and that anemia must be analyzed for successful treatment. A multidisciplinary approach to anemia caused by AUB is required in cases of severe anemia.